Relationships between vertical jump metrics and sprint performance, and qualities that distinguish between faster and slower sprinters - Washif, J. A.; Kok, L. Y. (Journal of Science in Sport and Exercise, 2022)
Purpose: This study aimed to investigate the relationships between vertical jump metrics and phases during a 60 m sprint. The variances in strength qualities between sprinters of different ability levels were also compared. Methods: Eighteen young male elite sprinters (age: 18.1 ± 1.3 years; stature: 1.72 ± 0.07 m; body mass: 66.3 ± 6.2 kg) were assessed for squat (SJ), countermovement (CMJ), drop (DJ), and standing long jumps, a maximal load back-squat, and a 60-m sprint from a block-start. The relationships between sprint performances with all variables were analysed using correlation and multiple regression while discriminative parameters between fast (100 m time: ~ 10.50 s) and slow (~ 11.00 s) sprint groups were assessed using independent t-tests. Results: Higher associations existed between vertical jumps and longer sprint distances, especially between SJ height and relative peak power with 10 m (r = - 0.47 and - 0.47, respectively), 30 m (- 0.71 and - 0.74), 60 m (- 0.76 and - 0.81), 10-30 m (- 0.80 and - 0.86), and 30-60 m (- 0.78 and - 0.84) sprint distances. Concurrently, variables such as relative maximal-strength, relative SJ parameters (height, peak force, and peak power), relative CMJ peak power, and reactive strength index (DJ from 35 cm height) had significant discriminative ability and correlations (P < 0.05) with sprint distances involving maximal velocity and flying-start. Additionally, a combination of SJ height and relative maximal-strength during back-squat accounted for 75% of the variance in 60 m sprint times. Conclusions: Relative measures of multiple strength metrics may provide better insight regarding factors that enhance sprint performance. Adequate maximal-strength, high explosive power, and reactive strength seem necessary to improve sprint performance in young male elite sprinters.